Systematic Review of Occupational Injuries and Illnesses in the Nigerian Mining Industry - Alaba, Olanrewaju Clement (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Nigerian mining sector (NMS) has been ranked as second industrial sector with numbers of occupational injuries and illnesses (OII) that pose serious social and economic impacts on workers and society. Meanwhile, little is known about the specific aspects of OII in the mining sector that have been studied in the literature. As a result, this study seeks to review the existing research on workers' OII with the intention of identifying the primary causes, symptoms, and influencing factors that may relate to a persistent rise of injuries and illnesses in the NMS. This is to determine the sector dynamic in relation to OII and provide stakeholders in the sector with lack data that are required for planning, implementation, and monitoring sustainable OII. The study employed widely accessible electronic databases (Science Direct, PubMed, Scopus, Google Scholar, and Web of Science) to perform a systematic review of peer-reviewed articles from 2010 to 2023. The causes, symptoms, and influencing factors of OII in the mining industry were highlighted in the compilation of pertinent data. The study search yielded 210 peer-reviewed publications with 70 publications retained after systematic screening and 20 were retained for final analysis. The study identified eight major causes, four body parts that are most harmed, and five primary symptoms of OII in the NMS. Also, the factors that influencing OII in NMS were classified as sociodemographic, behavioural and organizational/management factors. The study concluded that the use of personal protective equipment, provision of first aid and medical facilities, enactment of safety laws and policies and adequate safety training and supervision are the most common ways that can reduce the high rate of OII in the Nigerian mining sector.